Layanan Informasi berbasis Media Film Animasi untuk Mengembangkan Kemampuan Pemecahan Masalah Siswa SMK - Agus Wibowo; Zulia Awaliana Muslikhah; Nurul Atieka (Universitas Mathla'ul Anwar Banten, 2020)
THE USING OF ANIMATION FILM IN INFORMATION SERVICE TO IMPROVE PROBLEM SOLVING ABILITY OF VOCATIONAL SCHOOL STUDENTS. The use of animated film in information services aims to ensure that massage of information service can be well received by students, and students have good motivation in participating in services. This study aims to determine the effectiveness of film animation in information services to improve the ability to abilty of problem solve students of SMKN 3 Metro in the academic year 2019/2020. The research method used action research. The research subjects were 30 students. The research instrument is a test of problem solving skills. The results of the study were an increase in average achievement scores, in the first cycle the average score of students 'ability to solve problems was 19.5, and the second cycle was 24.19 and the difference in the scores of students' understanding scores in the second cycle with an ideal score of 7.05, in the first cycle the difference between the score with the ideal score is 11.75. Thus an increase between cycles I and II amounted to 4.70. The conclusion of the research is the animation film in information service effective to improve abilty problem solving of students SMKN 3 Metro academic year 2019/2020.